Design of polymerizable liquid crystal monomers for new side chain liquid crystalline polymers (SCLCPs) and their properties / Noordini binti Mohamad Salleh - Mohamad Salleh, Noordini (2014)
A new polymerizable monomer containing naphthalene ring in the mesogen with an ester linkage and various types of polymerizable monomers consisting of 1,4-disubstituted phenyl cores with a Schiff base and ester linkages have been designed and synthesized. These new Schiff base and ester based monomers were used to synthesize side chain liquid crystalline polymers (SCLCPs) via radical chain polymerization and atom transfer radical polymerization (ATRP). The chemical structure of monomers and polymers were confirmed by 1H NMR, 13C NMR and FTIR spectroscopies. The molecular weight and polydispersity of polymers as measured by GPC are in the range of 10,200 to 123,000 g/mol and from 1.16 to 2.79, respectively. The GPC analysis of the polymers also revealed the effects of polymerization method on polydispersity whereby polymers synthesized by ATRP showed narrow polydispersities compared to those synthesized by radical chain polymerization. Results from POM showed monomer containing naphthalene ring in the mesogen exhibited a nematic phase at 101.9°C and a smectic phase at 83.8°C while DSC suggested presence of a wide mesophase range between 50°C and 104°C. SAXS analysis showed a sharp scattering signal in the low q region (2.2 nm-1) indicating a typical smectic phase texture. Their polymers also exhibited both nematic and smectic phases appearing at 163°C and 149°C respectively as detected by DSC. As for the monomers with a Schiff base and ester linkages, a nematic phase at a temperature range of 40.0°C to 195.7°C was observed under POM which was further supported by DSC results. PXRD analysis also showed a typical nematic characteristic of a broad peak in the region 15-30° with d-spacing of 3-5 Å. Their polymers also exhibited nematic mesophase at a temperature range between 128.5°C and 232.0°C. From TGA analysis, all the resulting polymers were thermally stable below 389°C which is really excellent for the practical processing or for the possible use in devices. The absorption peaks from UV-Vis spectroscopy of these polymers varied from 300 to 400 nm, while the fluorescence peaks varied from 380 to 560 nm. The absorption maxima of UV-Vis and photoluminescence spectra were influenced by the electron donating substituent located at the side chain of polymers. All polymers have the characteristic of emissive polymers. The obtained HOMO and LUMO values of polymers are around -5.59 and -2.59 respectively which are close to that of the materials currently use in hole-transporting layers. The band gap values of polymers (3.03-3.18 eV) revealed that the newly synthesized SCLCPs could be potential candidate in photovoltaic applications. The rheological properties of the polymers showed that the dynamic shear moduli in a smectic phase tended to level off in the low frequency region. The steady shear viscosities of the smectic and nematic phase exhibited a shear thinning behavior over the shear rate tested. Meanwhile, a Newtonian behavior at low shear rate, followed by a strain hardening behavior at higher shear rate was observed in the isotropic phase.